fo027835: NCOS project 53, Deep well and water holes, Taiwan - 11.11.11
"Collection: Projectnummer: 53; Zwart-witfoto, van de waterpomp. NCOS project 53, Deep well and water holes, Taiwan, 1966-1972. Een realisatie van CRS; Catholic relief services. Land/Regio: Taiwan; Code: FORMOSE/66/EF; Projectnaam: Deep well and water holes; Series: Projectnummer: 53; Land/Regio: Taiwan; Code: FORMOSE/66/EF; Projectnaam: Deep well and water holes; FULL TEXT AVAILABLE AT AMSAB-ISH"